The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/fst.24219
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of exposure time to sodium chlorite (NaClO2) solution and packaging on postharvest quality of white button mushroom (Agaricus bisporus) stored at 4 °C

Abstract: Agaricus bisporus was washed with 1 g/L sodium chlorite (NaClD 2) (SC) solution for 30, 60 and 120 s, packed with a non-perforated polyvinyl chloride (PVC) film and stored at 4 °C for 12 days. Washing the mushrooms with the SC solution and packaging with the PVC film slowed down the change in colour and firmness of the mushrooms, but treating the mushrooms with the SC solution longer than 60 s adversely affected the mushroom texture. After 12 days of storage, the weight loss of the mushrooms packed with the PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We obtained similar results from the current study where the edible coating-treated samples showed lower weight loss than uncoated samples. In our study, disinfection was carried out with UV-C, and this gave more positive results in terms of weight loss than the application of NaClO 2 [30].…”
Section: Discussionmentioning
confidence: 79%
“…We obtained similar results from the current study where the edible coating-treated samples showed lower weight loss than uncoated samples. In our study, disinfection was carried out with UV-C, and this gave more positive results in terms of weight loss than the application of NaClO 2 [30].…”
Section: Discussionmentioning
confidence: 79%
“…Mushroom’s shelf-life is extremely limited for the distribution and the strategy of marketing due to the commercial losses. Consequently, several techniques were applied to prolong mushroom's shelf-life such as packaging, chilling, coating, nanocomposite films, washing with ascorbic acid, sodium chlorite, hydrogen peroxide, citric acid, and malic acid to act as antibrowning and antimicrobial resistance 5 , 6 . Chitosan is a non-toxic, natural food additive that is found in crustacean shells as shrimps and crabs which can prolong the shelf life due to effective antibacterial activity by forming a film around the fresh-cut produces or even the fruits as the whole bulk 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The minimum color differences were observed for CHSTiO 2 /TT80 (∆E* from 37.79 to 40.50), as a total color variation of more than two means a significant color difference. Tarlak et al [15] confirmed that color can be influenced by several factors such as enzyme oxidations and microbial population. Rok et al [25] confirmed that the reduction of the color attribute could be due to the polyphenolic compounds oxidation reactions.…”
Section: Weight Loss Ratio and Texture Measurementsmentioning
confidence: 98%
“…The color analysis was detected by a CR-400 (Konica Co., Japan), where L* value is the lightness that ranges from (0) black to (100) white; a* value ranges from (−120) green to (+120) red, while b* value ranges from (−120) blue to (+120) yellow at three different locations on mushroom samples [15].Total color difference (∆E*) was calculated by Equation 1:…”
Section: Color Analysismentioning
confidence: 99%
See 1 more Smart Citation